Transgenic nematodes as a model for Parkinson’s disease - Bodhicharla, Rakesh Kumar (2012)
Aggregation of the abundant neural protein α-synuclein contributes to cellular toxicity in Parkinson‘s disease. We have created transgenic nematodes carrying fusion constructs encoding human α-synuclein (S) tagged with YFP (V) and/or CFP (C) as a fluorescent marker. Using the unc-54 myosin promoter, a synuclein-YFP (unc-54::SV (NI)) fusion construct was abundantly expressed in the body wall muscles of Caenorhabditis elegans. Permanent integrated lines were successfully generated for unc-54::V (NI), unc-54::S+V (I), unc-54::SC+SV (I), unc-54::C+V (I), and unc-54::CV (I) using gamma irradiation. The outcrossed transgenic synuclein strains were radiation sensitive and have shorter life span and lower pharyngeal pumping compared to wild type N2 and unc-54::V (I) worms. Fluorescence Resonance Energy Transfer (FRET) was measured for all the transgenic strains. The unc-54::SC+SV (I) worms showed FRET signals intermediate between the negative (unc-54::C+V (I)) and positive (unc-54::CV (I)) control strains. Confocal images were taken to confirm the presence of FRET. FRET signals increase markedly during early adult life in unc-54::SC+SV (I) worms. RNA interference by feeding was performed in unc-54::SC+SV (I) worms to knock out the Hip-1 co-chaperone function, thereby increasing the FRET signal. unc-54::SC+SV (I) fusion worms were also exposed to pesticides such as chlorpyrifos and rotenone, and we observed an increase in the size and intensity of fluorescent aggregates thereby increasing the FRET signal. Finally we have quantified reactive oxygen species (ROS) for unc-54::SC+SV (I) fusion worms and NL5901 strains by using the H2DCF-DA assay, showing that ROS levels were increased by pesticide exposure.